The complete Buddhism for mothers - Napthali, Sarah, 1967-; Napthali, Sarah, 1967-; Napthali, Sarah, 1967-; Napthali, Sarah, 1967- (Crows Nest, N.S.W. : Allen & Unwin, 2010)
"Become a calmer and happier mother with The Complete Buddhism for Mothers. Parenthood can be a time of great inner turmoil for a woman yet parenting books invariably focus on nurturing children rather than the mothers who struggle to raise them. These books are different."--
Buddhism for mothers -- Buddhism for mothers of young children -- Buddhism for mothers of school children.
Featuring Sarah Napthali's three best selling books -- Cover.
Includes bibliographical references (pages 751-756) and index.
(NANGLIs
Keywords: Mothers -- Religious life; Parenting -- Religious aspects -- Buddhism; Child rearing -- Religious aspects -- Buddhism